Структура та складові механізму забезпечення корпоративної соціальної відповідальності акціонерного товариства - Манойленко, Олександр Володимирович; День, Цівень (Видавничий дім "Гельветика", 2022)
В статті визначено та узагальнено передумови зростання масштабів соціальної відповідальності корпоративного бізнесу та встановлено корпоративні особливості забезпечення соціальної відповідальності бізнесу в акціонерних товариствах. Визначено структуру та виявлено особливості взаємодії складових механізму забезпечення корпоративної соціальної відповідальності акціонерного товариства (корпорації). Встановлено складну суб’єктну природу формування корпоративної соціальної відповідальності бізнесу як результату досягнення збалансованості при задоволення як специфічних контрактних умов акціонерного інвестування, так і широкого кола суспільних зобов’язань акціонерного товариства. Доведено пріоритетність використання інституціонального інструментарію формування та підтримки механізму забезпечення корпоративної соціальної відповідальності акціонерного товариства. Виявлено особливий рефлексивний характер вимог щодо формування корпоративної культури в механізмі забезпечення корпоративної соціальної відповідальності акціонерного товариства.

The article defines and summarizes the prerequisites for the growth of the corporate business social responsibility scale. Corporate features of business social responsibility ensuring in joint-stock companies have been established. The structure and components interaction features of the joint-stock company's corporate social responsibility ensuring mechanism have been identified. The prerequisites for the corporation (an enterprise formed and operated in the organizational and legal form of a joint-stock company) subjectness achievement while establishing a set of business corporate social responsibility obligations has been determined. The connection nature between the target orientations of the joint-stock company stakeholder's involvement in corporate relations participation and corporate social responsibility obligations formation has been identified and systematized. The fundamental regularities of the joint-stock company stakeholder's reflexive interaction mental space formation have been considered through ensuring corporate social responsibility. The complex subject nature of the business's corporate social responsibility formation has been established as a consequence of achieving balance while satisfying both the equity investment specific contractual conditions and a joint-stock company's wide range of public obligations. The coalition nature of determining the joint-stock company's obligations and agreements regarding establishing the scope of corporate social responsibility has been revealed. The priority of the institutional toolkit usage to form and support the mechanism of ensuring a joint-stock company's corporate social responsibility has been proven. The unique reflexive nature of the requirements for the corporate culture mechanism forming within the joint-stock company's corporate social responsibility ensuring mechanism has been revealed. The crucial means for institutionalising a joint-stock company's requirements and obligations have been determined within the business's corporate social responsibility framework. The strategic aspects of a joint-stock company's corporate development management in the context of business's social responsibility ensuring have been summarized.
The mechanism for ensuring a joint-stock company's corporate social responsibility structure and components
Keywords: корпорація; акціонерне товариство; соціальна відповідальність; корпоративна соціальна відповідальність; корпоративна культура; механізм; corporation; joint-stock company; social responsibility; corporate social responsibility; corporate culture; mechanism